Effective immunosuppressive therapy in a patient with primary pulmonary hypertension. Issue 4 (1st April 1999) - Bellotto, F; Chiavacci, P; Laveder, F; Angelini, A; Thiene, G; Marcolongo, R
Abstract : The case history is described of a young woman who presented with primary pulmonary hypertension and non-specific inflammatory signs. The patient received prolonged immunosuppressive treatment with low dose methotrexate and prednisone without any vasodilator agent. After one year the pulmonary artery pressure fell from a mean value of 47 mm Hg to 30 mm Hg and there was a corresponding clinical response. This case suggests that, in patients with pulmonary hypertension of unknown origin, immunopathogenetic factors should be sought in order to consider the utility of immunosuppressive therapy.